2014
DOI: 10.4103/1319-2442.144322
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients with end-stage renal disease in Guinea

Abstract: This questionnaire-based study included 69 patients from the Republic of Guinea with end-stage renal disease (ESRD) and was conducted over 12 months. The factors that affected their quality of life (QoL) were determined. The included ESRD patients had an estimated creatinine clearance (CCr) of <15 mL/minute using MDRD formula. We used the SF36 question-naire and classified the results into two groups: Scores<50/100 as poor QoL and scores 50/100 as good QoL. Factors that determined the QoL were cessation of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Ka EHF, et al reported an average of 50.2 in Cotonou [7]. It was 48.8 years and 40.3 years respectively in Conakry [8] and Bamako [9]. The average age of our patients was broadly comparable to that of patients living in capitals of the countries of the sub-region.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Ka EHF, et al reported an average of 50.2 in Cotonou [7]. It was 48.8 years and 40.3 years respectively in Conakry [8] and Bamako [9]. The average age of our patients was broadly comparable to that of patients living in capitals of the countries of the sub-region.…”
Section: Resultssupporting
confidence: 56%
“…This result seems to be corroborated by that of Cisse MM, et al [6] in Dakar (sex ratio H/F = 0.9). On the other side, in the studies of Bah AO, et al and Diallo D, et al in Conakry and Bamako, men were more numerous with a respective sex ratio of 1.15 and 2 [8,9]. The DOPPS' study also reported a male predominance [10].…”
Section: Resultsmentioning
confidence: 88%
“…Ka et al reported an average of 50.2 in Cotonou [7]. It was 48.8 years and 40.3 years respectively in Conakry [8] and Bamako [9]. The average age of our patients was broadly comparable to that of patients living in capitals of the countries of the sub-region.…”
Section: Discussionsupporting
confidence: 55%
“…This result seems to be corroborated by that of Cisse et al [6] in Dakar (sex ratio H/F=0.9). On the other side, in the studies of Bah et al and Diallo et al in Conakry and Bamako, men were more numerous with a respective sex ratio of 1.15 and 2 [8,9]. The DOPPS' study also reported a male predominance [10].…”
Section: Discussionmentioning
confidence: 90%
“…The annual cost of haemodialysis has been estimated at $ 87 500 in the USA [18], between $ 22 000-55 000 in Nigeria [19,20] when the state subsidizes dialysis, the cost covered by patients is high and the majority cannot afford it. Morbidity and mortality are consequently high [32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%